Demand-Adapted Service Oriented Architecture Using Lego Model - Sami Hasan; Omar Sabraldeen Aziz (Iraqi Journal of Science, 2021)
Many developments happened in Service Oriented architecture models but with no details in its technology and requirement. This paper presents a new Service Oriented Architecture (SOA) to all Service Enterprise (SE) according to their demands. Therefore, the goal is to build a new complete architecture model for SOA methodologies according to current technology and business requirements that could be used in a real Enterprise environment. To do this, new types of services and new model called Lego Model are explained in details, and the results of the proposed architecture model in analyzed. Consequently, the complications are reduced to support business domains of enterprise and to start associating SOA methodologies in their corporate software.